Unequal Use of Social Insurance Benefits: The Role of Employers - Sarah Bana; Kelly Bedard; Maya Rossin-Slater; Jenna Stearns (Institute of Labor Economics (IZA), 2018)
California's Disability Insurance (DI) and Paid Family Leave (PFL) programs have become important sources of social insurance, with benefit payments now exceeding those of the state's Unemployment Insurance program. However, there is considerable inequality in program take-up. While existing research shows that firm-specific factors explain a significant part of the growing earnings inequality in the U.S., little is known about the role of firms in determining the use of public leave-taking benefits. Using administrative data from California, we find strong evidence that DI and PFL program take-up is substantially higher in firms with high earnings premiums. A one standard deviation increase in the firm premium is associated with a 57 percent higher claim rate incidence. Our results suggest that changes in firm behavior have the potential to impact social insurance use and thus reduce an important dimension of inequality in America.
Keywords: J31; J32; J38; 330; disability insurance; paid family leave; social insurance; firm premium